Pemberantasan Kanker di Yogyakarta - Soeripto Soeripto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1980)
Cimpaign against cancer is not only the duty of the medical professional but also the respon• sibility of the society. The activities of the Sardjito Teaching Hospital Cancer Team.